ANALYSIS OF THE LEGIBILITY OF MURABAá¸¤AH WAKALAH FINANCING PRACTICES AT PT. ACEH SHARIA BANK KCP DIPONEGORO - Aulil Amri; Linda Linda (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2022)
Murabaá¸¥ah financing is one of the most popular products in Islamic banking. Murabaá¸¥ah is defined as the activity of selling an item by confirming the purchase price to the buyer, the buyer pays a higher price than the previous price to make a profit. It can be seen that the essence of murabaá¸¥ah is that the bank provides non-money goods, where the bank should buy the goods needed by the customer and then sell them back to the customer at the selling price plus a profit. However, in practice the bank cannot do its own work, that is, it cannot provide the goods required by the customer; rather, the bank only provides funds for the purchase of the goods required through a wakalah contract with the customer in question. This study aims to find answers to the main issues, namely: how is the Fiqh Muamalah review of the practice of murabaá¸¥ah wakalah at PT. Bank Aceh Syariah KCP Diponegoro, what is the legitimacy of the practice of murabaá¸¥ah wakalah financing according to the DSN MUI fatwa and what is the mechanism for murabaá¸¥ah wakalah financing at PT. Bank Aceh Syariah KCP Diponegoro. The type that the author uses in this study is a descriptive analysis method. The data collection method in this study was data obtained from field research through interviews with the parties involved and taking references from a literature review. The results of this study show that there are still sharia principles, the pillars of murabaá¸¥ah which are not in accordance with fiqh muamalah and DSN MUI fatwa rules, where in the application of murabaá¸¥ah bil wakalah contracts at Bank Aceh Syariah KCP Diponegoro more often use murabaá¸¥ah and wakalah contracts in one contract. whereas in theory, the implementation of the wakalah contract must be carried out before the murabaá¸¥ah contract is carried out.